Analisis Sensitivitas Penurunan Konsolidasi Tanah Lunak di Pelabuhan Tanjung Emas Semarang: Studi Parametrik 1D Berbasis Data Sekunder - Anisa Diansisti; Zihni Ihkamuddin; Khabib Hidayat Raji; Rizki Bayu Ramadhan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The Port of Tanjung Emas in Semarang faces geotechnical challenges due to the prevalence of soft marine clay layers. This study employed an analytical-parametric computational method based on secondary data (desk study) synthesized from 15 indexed scientific publications (Scopus, SINTA, Google Scholar) from 2013 to 2024, covering geotechnical investigations at Semarang, Patimban, and Jakarta coastal areas. The analysis technique applied Terzaghi's one-dimensional consolidation equations with one-at-a-time (OAT) sensitivity analysis using the Normalized Sensitivity Index (NSI). All parameters were verified for physical consistency through soil phase relationships. Three scenarios, optimistic, realistic, and pessimistic, were analyzed. Results indicate a primary settlement range of 1.87–5.36 m for normally consolidated (NC) conditions and 1.11–3.83 m for overconsolidated (OC, OCR = 1.5) conditions. The 90% consolidation time without vertical drainage ranges from 9.5 to 88.3 years, while with 1.0 m-spaced Prefabricated Vertical Drain (PVD), it is reduced to 0.8–2.6 months. Estimated secondary compression adds 0.22–0.35 m in the optimistic and realistic scenarios. All scenarios exceed the maximum residual settlement limit of 300 mm per BS 6349 (BSI, 2021) and PIANC (2014) by 6–18 times. This study conclusively demonstrates that no construction scenario at Tanjung Emas Port is feasible without prior ground improvement, and the compression index (Cc) is the single most critical parameter (NSI = 1.00). Field validation is required.